Analisis Perbandingan Quantity Take Off Berbasis BIM dan BOQ Manual Pada Pekerjaan Struktur Gedung - Sarju; Hakim, Zaky Abad; Sukindrawati, Buddewi (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
Quantity take-off (QTO) calculation is an important component in cost estimation and material control in construction projects. Manual methods based on 2D drawings and Bill of Quantities (BOQ) are prone to inconsistencies due to the global volume addition approach and do not always follow the actual geometric cuts. This study compares the results of QTO based on Building Information Modeling (BIM) using Tekla Structures with manual BOQ on the structural work of the Tegal City Public Service Mall Building. The analysis focused on three materials: concrete, formwork, and reinforcement including foundation elements, beams, columns, slabs, and stair slabs. The results show that the total BIM volume produces 1,989.49 m³ of concrete, 6,857.70 m² of formwork, and 302,817.10 kg of reinforcement, while the BOQ recorded 2,025.37 m³, 7,305.17 m², and 303,502.10 kg. The deviations were 1.77%, 6.13%, and 0.23%, respectively. The differences were mainly influenced by automatic geometry truncation in the 3D model, the separation of specific elements such as pitlift walls, and inconsistent reinforcement rules (clear span, overlap, and development length) in manual calculations. These findings confirm that BIM-based QTO and BOQ can produce significant quantity differences in some elements, and identify recurring sources of deviations that can be used as a basis for quantity audits and improve calculation consistency across similar projects.